Miospore assemblages from the Silurian–Devonian boundary, in borehole A1-61, Ghadamis Basin, Libya - Rubinstein, Claudia Viviana (2002)
Well preserved and diversified miospore assemblages have been recorded from a relatively continuous sequence in borehole A1-61 which spans the Silurian–Devonian boundary in the northwestern part of the Ghadamis Basin, Libya. The sequence is represented by early Devonian Lochkovian beds of the Tadrart Formation that transgress onto the Silurian Ludlow-Pridoli beds of the upper part of the ‘Alternances Argilo-gréseuses’ Formation. The present work demonstrates a succession of miospore assemblages from closely sampled layers that have been stratigraphically dated as Ludlow–middle Pridoli and early Lochkovian by chitinozoans and acritarchs. Over 80 species of cryptospores and trilete spores have been identified. Modified detailed morphological interpretations are given. The miospore assemblages are correlated with miospore zonation schemes established for the type sequences of the Welsh Borderland, and those previously described from Libya. Early occurrences of some species as Streelispora newportensis on the western Gondwana plate, are put forward by comparison with the Old Red Sandstone continent. Phytogeographic and palaeobotanic implications based on these observations are discussed.